Two new species of Anisomeridium (lichenized Dothideomycetes, Ascomycota) from China - Zhang, Chao; Aptroot, André; Liu, Hua-Jie; Jiang, Shu-Hua (Phytotaxa, 2020)
The humid tropical and subtropical forests in South China harbour a rich diversity of crustose lichens. As a result of taxonomic studies of Anisomeridium, two species new to science are described. Comparisons and discussions with similar species are given. In addition, a key to the species of Anisomeridium in China is also provided.